A partially automated method for DNA extraction from marmoset hair follicles to avoid blood chimerism - Stendahl, Alexandra M.; Zhang, Qiangge; Lima, Ana C.; Mello, Curtis; Nemesh, James; Peterson, Sam; Castro, Jenna; Celino-Brady, Fritzie T.; Ray, Karina; Gao, Xian; Hou, Yuanyuan; Shen, Chenjie; et al. (Frontiers in Genetics, 2025)
Marmosets are valuable non-human primate models, however their unique reproduction results in high levels of blood chimerism, making blood unreliable for DNA sequencing. Hair follicles have lower levels of chimerism however DNA extraction from hair follicles is challenging due to the limited tissue. We developed a non-invasive, partially automated protocol for hair follicle collection and DNA extraction scalable to hundreds of samples. This method uses a proteinase K cell lysis solution in conjunction with Promega’s Maxwell RSC’s paramagnetic silica-based particles to purify DNA. We applied this protocol to samples collected from over 300 animals and from two different species. We were able to generate high quality libraries for whole genome sequencing (WGS) from approximately 150 hair follicles. Libraries built from >0.15 µg DNA had an average duplication rate of 0.19, analogous to libraries built from blood. Sequenced DNA had average chimerism rates of 2.3%. DNA extraction from hair follicles offers a reliable method for whole genome sequencing with minimal chimerism. The partial automation improves efficiency by reducing lab time and extraction variability. The protocol is applicable to a range of projects requiring low-input DNA sources or automated, high-throughput sample processing. Peer review data availability: Data on DNA yields and resulting whole genome sequencing libraries are provided as Supplementary Tables. The raw whole genome sequencing data produced from these libraries are archived online at the NIH Sequence Read Archive.